Anthropomorphism in comparative affective science: Advocating a mindful approach. (August 2020) - Williams, Lisa A.; Brosnan, Sarah F.; Clay, Zanna
Highlights: Anthropomorphism is the attribution of human-like capacities to non-human entities. Anthropomorphism is both beneficial and problematic for comparative research. We advocate a mindful approach to anthropomorphizing in comparative science. Abstract: Anthropomorphism is the attribution of human-like capacities and traits to non-human entities. Anthropomorphism is ubiquitous in everyday life and in scientific domains, operating both implicitly and explicitly as a function of the human lens through which we view the world. A rich history of work in psychology, animal behavior, cognitive science, and philosophy has highlighted the negative and, to a lesser degree, the positive implications of anthropomorphism. In this article, we aim to provide a nuanced perspective of how anthropomorphism impacts the work of comparative affective science. Specifically, we discuss three domains of empirical inquiry in which lessons can be drawn about the benefits and pitfalls of anthropomorphism: responses to death, inequity aversion, and prosocial behavior. On balance, we advocate a mindful approach to anthropomorphizing in comparative affective science, and comparative science more generally.